Virtual agent design model for a Higher Education Institution: A Kansei approach / Chandra Reka Ramachandiran - Chandra Reka , Ramachandiran (2018)
The rapid growth of Internet users and the diversity in application technologies have motivated research scholars and educators to design intelligent tools such as virtual agents as effective learning tools. However, the success of a learning tool relies primarily on the level of acceptance of the tool by the learners and the effectiveness of the tool itself. It must be noted that the first year experience is important to new learners as failing to optimize learners’ satisfaction can lead to higher attrition rate and it is proven that effective teaching tools are essential to retain these stakeholders in a Higher Education Institution (HEI). This research addresses the gap in the evidence on effective and affective design specifications of a teaching and learning tool that deploys virtual agents. To add on, the presence of design specific stereotypes that is very inclined to certain community does not adhere to the heterogeneous community of learners in Higher Education Institution. Therefore, this research aims to design and validate a Virtual Agent Design Model (VADM) using the Kansei approach to enhance learning in a Virtual Learning Environment (VLE) deployed in HEI that fosters multiculturalism. This research adapts the Kansei Engineering approach which is an emerging technology used to explore and validate the learner’s satisfaction. Further, this research highlights and validates the learner’s emotional experience based on the positive Kansei value of the designed virtual agents. The outcome proposes an affective design model for virtual agent design that caters to heterogeneous community in a HEI.